Deteksi Anemia dan Edukasi Gizi Remaja - Thaariq, Nurul Aziza Ath; Nadira, Nindy Audia; Sandra, Yuanita; Hidayati Wahyuni NS (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Stunting is a chronic malnutrition issue resulting from prolonged inadequate nutrient intake, and adolescents, as future parents, play a crucial role in its prevention. Data from the Riset Kesehatan Dasar (Riskesdas) surveys in 2007, 2013, and 2018 show a rising trend in anemia prevalence among adolescents. In 2018, 32% of adolescents in Indonesia were anemic, and in 2017, the prevalence in West Sumatra was 18.1%. Hemoglobin (Hb) testing is a vital method for early anemia detection. Additionally, providing nutritional education to teenage girls is essential for addressing anemia. This community service project aimed to detect anemia and offer nutritional education to teenage girls as a stunting prevention strategy. Conducted at SMA Negeri 12 Padang, the project involved Hb testing and nutritional education. Results revealed that 12% of 12th-grade female students were anemic. Nutritional education improved their knowledge, with average scores increasing from 19.97 before the intervention to 26.92 afterward. In conclusion, Hb testing and nutritional education are effective for early anemia detection and enhancing nutritional knowledge, crucial for preventing stunting.